EFFECTIVENESS MODEL OF LEARNING CYCLE â€œ5Eâ€AND STUDENT TEAM ACHIEVEMENT DIVISION (STAD) ON MATHEMATICS LEARNING OUTCOMES IN GRADE VIII OF EVEN SEMESTER IN SMP NEGERI 1 SEDAYU - Melina Asmanti Rahmi; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
ABSTRACTThe reason for the research that the learning process uses in SMP Negeri 1 Sedayu tends teacher-centered, Â students becoming passive and less involved in the learning process, and needed the model of learning that involved students. The objective of the study is to know the effectiveness model of the learning cycle â€œ5Eâ€ and STAD to student's mathematics learning outcomes. The population in this study were all students in grade VIII even semester SMP Negeri 1 Sedayu academic year 2015/2016. Technique sampling using a random sample of the class, obtainable class VIII A as experiment class I, class VIII E as experiment class II, and class VIII C as control class. The data collection technique is to use the test. The research instrument is the mathematics result test in the form of a double helix. Instrument test includes validity, distinguishing capacity ad reliability testing. Analysis of the data used is the prerequisite test analysis consist of a normality test and homogeneity test, and the hypothesis test consists of test F and tests Least significant different (LSD). The result on a significant level 5% and df = (2,87) shows (1) there is a different result of the mathematics learning uses the model of learning cycle â€œ5Eâ€, the model of learning STAD, and model of learning conventionally. This is shows with value fcount = 12,1253 > ftable Â > Â and (2) the results mathematics learning of the students that use the model of learning cycle â€œ5Eâ€ better than learning process uses the model of learning STAD and result from mathematics learning of the students that use the model of learning STAD better than learning process uses the model of learning conventionally. This result shows with hypothesis test LSD which is significant level 5% and 87 degrees of freedom is obtained in case I because Â Â rejected, it's mean thatÂ  Â . In case II Â Â rejected, it is mean that . While in case III Â Â rejected, it's mean that . While can concludes as follow .